Évaluation des Connaissances, Attitudes et Pratiques des Médecins Généralistes concernant l'Ostéoporose - BABA MOHAMMED (Université Amar Télidji Laghouat, 2023)
Osteoporosis is a systemic skeletal disease often referred to as the silent epidemic of the 21st century. It is characterized by low bone mass and altered bone microarchitecture, leading to increased bone fragility and susceptibility to fractures. Fractures typically occur after minor trauma, such as a tripping or a fall from a standing position, and are often diagnosed during emergency department visits. Unfortunately, many patients do not receive continuous medical follow-up beyond the fracture episode, resulting in underdiagnosis and inadequate management of the disease. General practitioners have a crucial role to play in the assessment and management of osteoporosis. Surveys conducted among primary care physicians in various countries have highlighted areas for improvement in the management of osteoporosis.
Une Étude Transversale Réalisée de septembre 2022 à Mars 2023 auprès des Médecins Généralistes à Laghouat
135 p.